The role of emotional states and mental techniques in dancesport: A systematic review - Sara ALIBERTI; Gaetano RAIOLA; Domenico CHERUBINI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: Psychological states during competition seem to be an important factor to determine successful performance. Therefore, the analysis of emotions is essential to understand how emotions can support sports performance. This systematic review aimed to summarize the studies examining the influence of emotional states on dancesport (DS) performance and the use of mental techniques to improve psychological preparation to face the competition. Material and methods. Web of Science, Scholar, Scopus and Pubmed databases were used to search studies. The screening process was summarized within the PRISMA 2020 flowchart. Results. Only 9 articles met our inclusion criteria. The results demonstrated that anxiety was the most common pre-competition emotional state of high-level DS athletes, followed by stress, arousal, concentration and self-confidence. The mental techniques of psychological preparation were mental contrasting, self-talk, bio/neurofeedback, the nine-step connection model and Cantón's Giraffe model. Emotional states can affect DS performance both positively and negatively; therefore, it is important to monitor these factors in order to improve one's performance. Several mental techniques can be used to improve the athlete psychological states. Conclusion. Further research is needed to better understand the effects of these parameters on DS performance, especially in mid-low-level athletes.